Etika Belajar Mengaji Melalui Youtube Menurut Perspektif Hadis Nabi - Nur Shofiyati; Dwi Umar Jaya; Akhmad Supriadi; Taufik Warman; Agisna Fadilawati; Nabilah Cipta Rahman (LPPM Institut Pendidikan Nusantara Global, 2025)
The advancement of digital technology, particularly the YouTube platform, has transformed the paradigm of learning to read the Qur'an, raising questions regarding ethics and moral values within the Islamic context. This study aims to examine the ethics of learning Qur’anic recitation through YouTube from the perspective of the hadiths of Prophet Muhammad (peace be upon him), and to identify relevant ethical principles in online learning practices. This research employs a qualitative method with a literature study approach, using hadiths and Islamic scholarly texts as primary sources. The population includes hadith compilations and related literature, analyzed descriptively and hermeneutically. Data were collected through document analysis and interpreted to identify ethical values and principles in seeking knowledge. The findings reveal five key principles: sincerity of intention, selectivity in choosing teachers, proper listening etiquette, repetition, and application of knowledge, as essential in digital learning to align with the teachings of the Prophet. The study concludes that although digital platforms provide easier access, ethical values must be upheld, and the role of teachers and direct interaction remains vital for instilling moral and spiritual foundations. The study recommends further empirical research to develop ethical learning models aligned with the hadith tradition.